2023
DOI: 10.1186/s12903-023-02857-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of internal fit and marginal gap of endocrowns using lithium disilicate and polyether ether ketone materials - an in vitro study

Abstract: Background The aim of the study was to investigate the effect of material and occlusal preparation design on the internal fit and marginal gap of endocrowns made of Polyether ether ketone (PEEK) and lithium disilicate. Methods 32 endocrowns were fabricated on prepared mandibular molars and divided into two groups (n = 16) according to the material. Group L: lithium disilicate and Group P: PEEK. Each group was further subdivided into two subgroups (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…All included studies were in vitro studies [ 12 28 ]. The highest number of publications, 7 studies (41%), was from the year 2023 [ 12 15 , 19 , 20 , 22 ], followed by years between 2020 and 2022, with 6 studies (35%) [ 20 , 21 , 25 28 ]. Fourteen (76%) studies reported using natural teeth [ 12 15 , 17 23 , 25 27 ], 12 studies (71%) were for mandibular arches [ 13 17 , 19 – 20 , 22 25 , 27 ], and 11 studies (65%) were for molars [ 13 16 , 19 , 22 25 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All included studies were in vitro studies [ 12 28 ]. The highest number of publications, 7 studies (41%), was from the year 2023 [ 12 15 , 19 , 20 , 22 ], followed by years between 2020 and 2022, with 6 studies (35%) [ 20 , 21 , 25 28 ]. Fourteen (76%) studies reported using natural teeth [ 12 15 , 17 23 , 25 27 ], 12 studies (71%) were for mandibular arches [ 13 17 , 19 – 20 , 22 25 , 27 ], and 11 studies (65%) were for molars [ 13 16 , 19 , 22 25 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The highest number of publications, 7 studies (41%), was from the year 2023 [ 12 15 , 19 , 20 , 22 ], followed by years between 2020 and 2022, with 6 studies (35%) [ 20 , 21 , 25 28 ]. Fourteen (76%) studies reported using natural teeth [ 12 15 , 17 23 , 25 27 ], 12 studies (71%) were for mandibular arches [ 13 17 , 19 – 20 , 22 25 , 27 ], and 11 studies (65%) were for molars [ 13 16 , 19 , 22 25 , 27 , 28 ]. LDGC and zirconia were the most common all-ceramic materials used for endocrown constructions, with 35% and 30%, respectively, and either alone or in comparisons with other all-ceramic materials.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations